2023
DOI: 10.4193/rhin22.361
|View full text |Cite
|
Sign up to set email alerts
|

Development and multicenter validation of a novel radiomics-based model for identifying eosinophilic chronic rhinosinusitis with nasal polyps

et al.

Abstract: BACKGROUND: Reliable noninvasive methods are needed to identify endotypes of chronic rhinosinusitis with nasal polyps (CRSwNP) to facilitate personalized therapy. Previous computed tomography (CT) scoring system has limited and inconsistent performance in identifying eosinophilic CRSwNP. We aimed to develop and validate a radiomics-based model to identify eosinophilic CRSwNP. METHODS: Surgical patients with CRSwNP were recruited from Tongji Hospital and randomly divided into training (n = 232) and internal val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Accordingly, severe infiltration of inflammatory cells in sinonasal mucosa, excessive proinflammatory cytokine accumulation, and tissue remodeling were regarded as the major pathogenetic mechanisms in the recurrent CRS. 41 , 42 It was worth noting that uric acid pathway activation could promote innate cytokine production and group 2 innate lymphoid cell (ILC2s) accumulation, which contributed to aggravating Th2 immune responses. 43 , 44 Emerging evidence has suggested that hyperuricemia can increase oxidative stress levels within the airway mucosa, leading to increased generation of free radicals, which in turn may trigger inflammatory responses, epithelial-mesenchymal transition, and tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, severe infiltration of inflammatory cells in sinonasal mucosa, excessive proinflammatory cytokine accumulation, and tissue remodeling were regarded as the major pathogenetic mechanisms in the recurrent CRS. 41 , 42 It was worth noting that uric acid pathway activation could promote innate cytokine production and group 2 innate lymphoid cell (ILC2s) accumulation, which contributed to aggravating Th2 immune responses. 43 , 44 Emerging evidence has suggested that hyperuricemia can increase oxidative stress levels within the airway mucosa, leading to increased generation of free radicals, which in turn may trigger inflammatory responses, epithelial-mesenchymal transition, and tissue remodeling.…”
Section: Discussionmentioning
confidence: 99%
“… 45 Simultaneously, it amplifies eosinophilic inflammation by recruiting and facilitating the migration of eosinophils into tissues. 46 , 47 To explore the role of CSF1R in driving M2 polarization and its association with CRSwNP recurrence, we conducted an overexpression of CSF1R in macrophages. We observed that up-regulation of CSF1R enhanced macrophage M2 polarization and secretion of IL-12 and TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…Its diagnosis primarily relies on pathological tissue section examination and eosinophil count, which is invasive and subject to certain subjectivity. 34 , 35 Although previous studies have identified several potential biomarkers for predicting eCRSwNP, such as serum metabolomics, 36 nasal microbiota, 37 and the peripheral blood lymphocyte-to-eosinophil ratio, 38 their sensitivity and specificity remain relatively constrained, hindering their adoption in clinical settings. Therefore, the exploration of objective biomarkers for eCRSwNP is still a current research focus, which will contribute to achieving personalized precision treatment.…”
Section: Discussionmentioning
confidence: 99%